Insights into diurnal variations of advanced hemodynamic parameters in ambulatory individuals enabled by a photoplethysmography-based wearable monitor. (3rd October 2022) - Nachman, D; Kolben, Y; Carmon, E; Hazan, E; Goldstein, N; Eisenkraft, A; Fons, M; Amir, O; Asleh, R; Gepner, Y
Abstract: Background: Recent technological developments enable non-invasive monitoring of advanced hemodynamic parameters, allowing big data-driven insights on diurnal changes for the first time. This study aimed to describe the trends of multiple advanced cardiovascular parameters among ambulatory individuals using a medical grade wearable monitor. Methods: Common and advanced cardio-respiratory parameters were monitored for 24 hours in ambulatory volunteers using a photoplethysmography-based wearable monitor. The multi vital ambulatory monitoring (MVAM) included stroke volume (SV), cardiac index (CI), systemic vascular resistance (SVR), blood oxygen saturation (SpO2), respiratory rate (RR), systolic (SBP) and diastolic blood pressure (DBP), mean arterial pressure (MAP), pulse pressure (PP), and heart rate (HR). Diurnal variations were evaluated among all participants, and analyses were stratified based on sex, age, and body-mass index (BMI). Results: A total of 256 participants were included in the analysis. All measured parameters showed significant (p<0.001) diurnal changes. Nighttime values were lower excluding RR and SVR, reaching the nadir at 5 am, and then increasing to a maximum at 10 am, plateauing, and then gradually declining from 7 to 8 pm. CI demonstrated a reduction of 0.6 L/min/m 2 (20%), while SVR demonstrated the opposite trend and was higher during the night increasing by up to 212 dynes/sec/cm 5 (16%). Females demonstrated higher HR and CI with lower SVR during daytime and nighttime. Obese participants (BMI >30 kg/m 2 ) had a higher SBP and DBP, and lower SV and CI. SVR was higher among the elderly. Conclusions: Diurnal changes using MVAM corresponding with awake-sleep hours were noticed in the monitored parameters and differed between sex, age, and BMI groups. This suggests that wearable monitoring platforms could shed more light on hemodynamic changes in subgroups, and might help with future efforts to provide tailored personalized medicine and pre-symptomatic diagnosis and prevention. Funding Acknowledgement: Type of funding sources: None.